2017
DOI: 10.1111/ajr.12375
|View full text |Cite
|
Sign up to set email alerts
|

Health professional students' rural placement satisfaction and rural practice intentions: A national cross‐sectional survey

Abstract: Objective: The aim of this study was to profile students undertaking placements at University Departments of Rural Health (UDRHs) and investigate factors affecting students' satisfaction and intention to enter rural practice. Design: Cross-sectional survey comprising 21 core questions used by all UDRHs. Setting: Eleven UDRHs across Australia that support students' placements in regional, rural and remote locations. Participants: Medical, nursing and allied health students who participated in UDRH placements be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(108 citation statements)
references
References 15 publications
6
101
1
Order By: Relevance
“…12,24,30,32,34,43 However, these articles have limitations as most of them investigate intention immediately after exposure to rural practice and do not follow through to actual practice location after graduation. Although this scoping review has identified 31 articles with some relevance to this area, many of these articles are narrative and some have limitations in terms of very small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,24,30,32,34,43 However, these articles have limitations as most of them investigate intention immediately after exposure to rural practice and do not follow through to actual practice location after graduation. Although this scoping review has identified 31 articles with some relevance to this area, many of these articles are narrative and some have limitations in terms of very small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…The results from all of these articles have indicated that rural placements have had a positive influence on students' intention to work rurally. 12,24,30,32,34,43 However, these articles have limitations as most of them investigate intention immediately after exposure to rural practice and do not follow through to actual practice location after graduation. 12,30,32,34,43 Consequently, it cannot be determined that rural clinical placements are having any impact on increasing pharmacist recruitment or retention in rural and remote locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, King et al 6 found that students who reported that their rural clinical placements had a positive impact on their well‐being were more likely to have intentions for rural internship. Furthermore, it was reported that positive experiences amongst a national sample of health professional students on rural placements were associated with increased intention to practise rurally in the future 10 . Drawing on these research findings, the current study was based on two premises: (a) that positive placement experiences are predictors of medical students’ intention to practise rurally in the future, and (b) that discovering the predictors of student well‐being on rural placements and addressing these issues in practice may improve students’ rural placement experiences and health 6,10,11 …”
Section: Introductionmentioning
confidence: 99%